Challenges of and opportunities for protecting European soil biodiversity. Issue 5 (19th July 2022) - Zeiss, Romy; Eisenhauer, Nico; Orgiazzi, Alberto; Rillig, Matthias; Buscot, François; Jones, Arwyn; Lehmann, Anika; Reitz, Thomas; Smith, Linnea; Guerra, Carlos A.
Abstract: Soil biodiversity and related ecosystem functions are neglected in most biodiversity assessments and nature conservation actions. We examined how society, and particularly policy makers, have addressed these factors worldwide with a focus on Europe and explored the role of soils in nature conservation in Germany as an example. We reviewed past and current global and European policies, compared soil ecosystem functioning in‐ and outside protected areas, and examined the role of soils in nature conservation management via text analyses. Protection and conservation of soil biodiversity and soil ecosystem functioning have been insufficient. Soil‐related policies are unenforceable and lack soil biodiversity conservation goals, focusing instead on other environmental objectives. We found no evidence of positive effects of current nature conservation measures in multiple soil ecosystem functions in Europe. In German conservation management, soils are considered only from a limited perspective (e.g., as physicochemical part of the environment and as habitat for aboveground organisms). By exploring policy, evidence, and management as it relates to soil ecosystems, we suggest an integrative perspective to move nature conservation toward targeting soil ecosystems directly (e.g., by setting baselines, monitoring soil threats, and establishing a soil indicator system). Resumen: La biodiversidad del suelo y las funciones ambientales relacionadas se dejan de lado en la mayoría de las evaluaciones de la biodiversidad y de las acciones de conservación de la naturaleza. Analizamos cómo la sociedad, y particularmente los formuladores de políticas, han abordado estos factores a nivel mundial con un enfoque en Europa y exploramos como ejemplo el papel de los suelos en la conservación de la naturaleza en Alemania. Revisamos las políticas mundiales y europeas en el pasado y en la actualidad, comparamos el funcionamiento ambiental del suelo dentro y fuera de las áreas protegidas y examinamos el papel de los suelos en la gestión de la conservación por medio del análisis de textos. La protección y la conservación de la biodiversidad y el funcionamiento ambiental del suelo han sido insuficientes. Las políticas relacionadas con el suelo son inaplicables y carecen de objetivos de conservación para su biodiversidad, pues se enfocan más bien en otros objetivos ambientales. No descubrimos evidencias de los efectos positivos de las medidas actuales de conservación en múltiples funciones ambientales del suelo en Europa. En la gestión alemana de la conservación, los suelos sólo se consideran desde una perspectiva limitada (p. ej.: como una parte físico química del ambiente y como hábitat para los organismos que habitan por encima de él). Mediante la exploración de la política, evidencias y gestión conforme se relaciona con los ecosistemas del suelo, sugerimos una perspectiva integrada para dirigir a la conservación hacia el enfoque directo sobre los ecosistemas del suelo (p. ej.: al establecer líneas base, monitorear las amenazas para el suelo y establecer un sistema indicador del suelo). 欧洲土壤生物多样性保护的挑战和机遇: 【摘要】 大多数生物多样性评估和自然保护行动都忽视了土壤生物多样性及相关生态系统功能。我们研究了社会, 特别是政策制定者, 如何在以欧洲为重点的全世界范围内应对这些问题, 并以德国为例探讨了土壤在自然保护中的作用。本研究综述了过去与现在全球及欧洲的政策, 比较了保护区内外的土壤生态系统功能, 并通过文本分析研究了土壤在自然保护管理中的作用。我们发现, 对土壤生物多样性和土壤生态系统功能的保护仍有欠缺。与土壤有关的政策难以实施, 且缺少土壤生物多样性保护目标, 已有的保护目标更多地集中在其他环境目标上。我们没有发现欧洲目前的自然保护措施对多种土壤生态系统功能产生积极影响的证据。德国的保护管理仅从有限的角度考虑土壤因素(如作为环境的物理化学部分和地上生物的栖息地)。通过探讨与土壤生态系统有关的政策、证据和管理, 我们提出了一个综合性观点, 以促进自然保护朝着直接针对土壤生态系统的方向发展, 如通过设定基线、监测土壤威胁, 以及建立土壤指标体系。【翻译:胡怡思;审校:聂永刚】